A responsabilidade internacional das empresas transnacionais por violação dos direitos humanos de grupos em situação de subalternidade por meio do cosmopolitismo intercultural - Damasceno, Gabriel Pedro Moreira (Universidade do Vale do Rio dos Sinos, 2022)
One of the great challenges faced by victims of human rights violations concerns the absence of effective norms of accountability of transnational corporations - TNCs when they are responsible for such violations. This challenge is even more intensified when the victims are people or groups belonging to subaltern groups due to the colonial matrix of power. An attempt has been made to understand the reasons why TNCs are not held accountable, as this impunity impacts individuals, groups and even states in the Global South. In this sense, this research intends to answer the question: can international law become a possible way to hold TNCs responsible for human rights violations of groups in a situation of subalternity? The research problem carried out here has two hypotheses: the zero hypothesis, which corresponds to the possible identification that it is not possible to carry out the accountability of TNCs that violate the human rights of groups in a situation of subalternity through international law; the second, hypothesis one, is that, as long as the orthodox conception of history is broken and intercultural cosmopolitanism is assumed as a fundamental basis of this right, it would be possible, through international law, to build accountability mechanisms for TNCs that violate rights humans from groups in a situation of subalternity, thus constituting an alternative to the zero hypothesis. This research was divided into two parts, each one responsible for verifying the hypotheses presented. From a dialogic analysis between decolonial theories with the third-world approaches to international law - TWAIL - and cosmopolitan theories, through the adoption of an intercultural cosmopolitanism as the foundation of international law, the possibility of international accountability of TNCs that violate human rights.

Uno de los grandes desafíos que enfrentan las víctimas de violaciones de derechos humanos se refiere a la ausencia de normas efectivas de rendición de cuentas de las empresas transnacionales - ETN cuando son responsables de dichas violaciones. Este desafío se intensifica aún más cuando las víctimas son personas o grupos pertenecientes a grupos subalternos debido a la matriz colonial de poder. Se ha hecho un intento por comprender las razones por las cuales las transnacionales no rinden cuentas, ya que esta impunidad afecta a individuos, grupos e incluso estados en el Sur Global. En este sentido, esta investigación pretende responder a la pregunta: ¿puede el derecho internacional convertirse en una vía posible para responsabilizar a las ETN por violaciones de derechos humanos de grupos en situación de subalternidad? El problema de investigación aquí realizado tiene dos hipótesis: la hipótesis cero, que corresponde a la posible identificación de que no es posible llevar a cabo la rendición de cuentas de las ETN que violan los derechos humanos de los grupos en situación de subalternidad a través del derecho internacional; la segunda, hipótesis uno, es que, en tanto se rompa la concepción ortodoxa de la historia y se asuma el cosmopolitismo intercultural como base fundamental de este derecho, sería posible, a través del derecho internacional, construir mecanismos de rendición de cuentas para las ETN que violan derechos humanos de grupos en situación de subalternidad, constituyendo así una alternativa a la hipótesis cero. Esta investigación se dividió en dos partes, cada una encargada de verificar las hipótesis planteadas. A partir de un análisis dialógico entre las teorías decoloniales con los enfoques tercermundistas del derecho internacional - TWAIL - y las teorías cosmopolitas, pasando por la adopción de un cosmopolitismo intercultural como fundamento del derecho internacional, se plantea la posibilidad de la rendición de cuentas internacional de las transnacionales que violan los derechos humanos. Palabras clave: Colonialidad; Imperialidad; Colonialidad
Keywords: Colonialidade; Imperialidade; Colonialidade interna; Responsabilização internacional de empresas transnacionais; Cosmopolitismo intercultural; Coloniality; Imperiality; Internal coloniality; International accountability of transnational companies; Intercultural cosmopolitanism; Colonialidad; Imperialidad; Colonialidad interna; Responsabilidad internacional de las empresas transnacionales; Cosmopolitismo intercultural; ACCNPQ::Ciências Sociais Aplicadas::Direito